A Study Of The Late Neogene Tectonic Deformation of the Kayu Ajaran Region, South Bengkulu, Bengkulu - Andrian, Fikri; Sutriyono, Edy (Universitas Negeri Gorontalo, 2025)
This study investigates the tectonic deformation history of the Kayu Ajaran area in South Bengkulu through integrated geological structure mapping and Digital Elevation Model (DEM)-based lineament interpretation. The research focuses on reconstructing the sequence of tectonic events that occurred during the Late Neogene within the Bengkulu Forearc Basin, a region known for its complex tectonic setting. Fieldwork and remote sensing analysis identified twelve major structural features, comprising eight folds and four faults. These structures predominantly trend northwest–southeast (NW–SE), indicating a compressional stress regime oriented northeast–southwest (NE–SW). The fold geometries, ranging from upright to steeply inclined types, and fault types, including thrust, reverse, and strike-slip, suggest the reactivation of earlier Paleogene extensional structures during the Neogene compressional phase. Stereographic and kinematic analyses were used to determine the orientation of principal stress axes (σ1, σ2, σ3), supporting the interpretation of inversion tectonics. DEM-based lineament analysis enhanced the identification of structural trends and fault zones, especially in areas with limited outcrop exposure. The study provides a clearer understanding of the progressive tectonic deformation in the region and fills critical gaps in the structural characterization of the Kayu Ajaran area. These results contribute to broader regional tectonic models of southwest Sumatra.